Applying the DSM-5 Alternative Model of Personality Disorders and the Shedler-Westen Assessment Procedure to the Classic Case of “Madeline G.”: Novice and Expert Rater Convergences and Divergence - Garner, Alisa R.; Blocher, Natalie; Tierney, David; Baumgardner, Megan; Watson, Alayna; Romero, Gloria; Skadberg, Rebecca; Younginer, Taylor; Waugh, Mark H. (Frontiers in Psychology, 2022)
Prior research supports the learnability of the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition Alternative Model of Personality Disorders (AMPD). However, researchers have yet to compare novice ratings on the AMPD’s Level of Personality Functioning Scale and the 25 pathological personality traits with expert ratings. Furthermore, the AMPD has yet to be examined with the idiographic Shedler-Westen Assessment Procedure (SWAP). We compared the aggregated AMPD clinical profile of a group of psychology doctoral students who learned the AMPD to high levels of reliability to that of an expert rater using the crucible of the classical case of “Madeline G.” Examination of AMPD and SWAP ratings of “Madeline G.” revealed excellent overall concordance but suggests that novice raters tend to perceive lower levels of personality impairment.